PRENATAL INFECTION AT THE HUMAN PAPILLOMA VIRUS INFECTION AT PREGNANT WOMEN - N. Yu. Katkova; N. A. Kabatin; O. V. Kachalina (IRBIS LLC, 2016)
The problem of infectious diseases during pregnancy continues to be relevant. It could be connected with possible complications during pregnancy and with the probability of the risk of intrauterine infection. One of the most common infections in the world, including among women of reproductive period is human papilloma virus (HPV) infection. There is lack of detailed information on risk factors for intrauterine fetal contagion with HPV infection. Objectives. Study objective was to reveal risk factors of vertical transfer of HPV. Materials and methods. 102 pregnant women with various forms of a papilloma virus infection are examined using real time polymerase chain reaction (PCR). Exclusion criteria were invasive and preinvasive cervical cancer, HIV infection, with concomitant CMV or HSV infection. Results. The general frequency of prenatal HPV infection was 14.7%. Risk factors of vertical transmission: high virus load, squamosus intraepitelial lession, abnormality vaginal biocenosis, reduction of secretory immunoglobulin in cervical mucus, increase in duration of vaginal birth and duration of the waterless period. There is not found correlation between age and social risk factors, parity, physical state and the frequency of HPV transmission from mother to child (p>0.05), as well as statistically significant impact on the incidence of fetal infection, complications of pregnancy and delivery method (p>0.05).